On a novel type of generalized simulation functions with fixed point results for wide Ws-contractions - Roldán López de Hierro, Antonio Francisco; Sintunavarat, Wutiphol (Nonlinear Analysis: Modelling and Control, 2025)
One of the most significant hypotheses in fixed point theory is the nonexpansivity condition of contractive mappings. This property is crucial as operators that do not satisfy this criterion may lack fixed points. In this paper, we propose a novel condition that, within the appropriate framework, can obviate the necessity of imposing the nonexpansivity requirement in the initial hypotheses. By employing this new condition, we illustrate how innovative results can be derived in this area. Finally, we examine the existence and uniqueness of a solution for an elastic beam equation with nonlinear boundary conditions grounded in the introduced fixed point results.